Bioinformatics and modelling studies of FhuD, the periplasmic siderophore binding protein from the plant pathogen Erwinia amylovora - Sharda Bharti; Lavinia Carlini; Alfonso Esposito; Stefano Benini (PLoS ONE, 2025)
Erwinia amylovora, a Gram-negative phytopathogenic bacterium, is the etiological agent of fire blight in apples and pears. Key virulence factors include the exopolysaccharide amylovoran, the type III secretion system, and siderophore-mediated iron uptake. Within the iron uptake pathway, the periplasmic siderophore binding protein FhuD, unique to Erwinia species infecting Rosaceae, plays a vital role in transporting iron-loaded siderophores to the inner periplasmic membrane, making it a crucial target for structural and functional characterization. This article presents the predicted 3D model of FhuD from E. amylovora (FhuD_Ea), along with the sequence analyses and structural comparison of its homologs from eight organisms whose structures are available in the PDB. We also performed bioinformatics analysis on protein sequences of 145 orthologs. Despite the low sequence identity, the homologs exhibited similar structures, with consistent ligand binding clefts. Nine conserved residues, primarily located in the N-terminal domain, were identified, with the exception of GLY 202 (in the C-terminal domain of FhuD_Ea). Among orthologs, ILE 88 emerged as a notably conserved residue in the N-terminal region, while TRP 64, though often positioned in the binding cleft, was not universally conserved. A phylogenetic tree based on 145 orthologs revealed no distinct grouping between Gram-positive and Gram-negative bacteria, suggesting that the periplasmic binding protein retains similar structural and functional characteristics across diverse bacterial lineages. The apparent lack of universally conserved residues in the ligand-binding pocket suggests functional flexibility, allowing FhuD to recognize siderophores with similar chemical features rather than identical structures. Molecular docking analyses further supported this hypothesis, showing that FhuD_Ea preferentially binds hydroxamate-type siderophores like ferrioxamine, but also accommodates structurally related ligands such as coprogen, with even greater binding affinity. These findings point to an adaptable binding mechanism that may enhance iron acquisition under varying environmental conditions.